Antimicrobial activity of the volatile substances from essential oils - Mareshah Abers; Sydney Schroeder; Linna Goelz; Adrienne Sulser; Tiffany St. Rose; Keely Puchalski; Jeffrey Langland (BMC, 2021)
Abstract Background Essential oils are volatile and lipophilic liquid extracts made from plants as secondary metabolites that can be obtained by distillation. To date, several studies have investigated the direct antimicrobial activity of liquid essential oils. However, this study investigated the antimicrobial properties of the volatile substances present in various essential oils. Methods A modified zone of inhibition protocol was developed using agar petri dishes with a center glass vial to allow evaporation and aerosolization of the potential active constituents from essential oils. In total, nineteen essential oils were tested against five Gram positive bacterial species, five Gram negative bacterial species and one fungi. Results This study found potent antimicrobial activity from the volatile constituents of several essential oils. Rosemary, tea tree, and cassia volatiles were found to be the best broad-spectrum antibacterial agents, whereas clove volatiles had almost no antimicrobial activity. Conclusions These results support the anecdotal historical evidence of the antimicrobial activity of the volatile constituents essential oils. Modern medical implications for this work may be related to the use of aromatic essential oils for respiratory or dermatological infections.